Resilience and Transpersonal Psychology: enhancing values, action and spirituality: DOI: 10.15343/0104-78092012362291302 - Pereira Simão, Manoel José (2012)
We see more and more news in the media about increasing cases of violence in robberies, murders, crimes and corruption.Society passes through a revision of values where education and discipline for caring for humans use several theses aiming to discoverefficient ways and tools for promoting a culture of peace based on values. Integral health promotion and the construction ofa stronger community based on humane actions and human values may be favored by programs and projects based on a Transpersonalapproach that revalues the importance of transcendence and spirituality inherent to human psyche. Many researches inthis field are based on the question: How people exposed to risky situations and experiences harmful for their development areable to adjust to daily demands? The proposal of this article is to understand the grounds of transpersonal psychology integrativeapproach (Saldanha 2006) and its application for strengthening resilience mechanisms in human groups in general and groups ofpatient in a psychology clinic. For doing this we present the concepts on resilience and after mention the main bases of transpersonalityapplied to the development of human values and integration of spirituality to human condition and health.